A case study exploring the McDonald's redesign towards an upgraded fast food experience - Lorredo, Jasmine Francesca G.; Faustino, Johanna Victoria Acab (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT Since McDonald?s Philippines? 30thanniversarylast 2011, the company has been establishing new grounds to its overall design. Through a series of store renovations and newly-opened branches, it is aiming to portray a fresher, more comfortable and more modern McDonald?s experience for its customers. This is a case study focused on McDonald?s Greenhills, and was conducted to gauge the effectiveness of McDonald?s redesign in providing its customers with an improved dining and lounging experience that shifts away from the ?eat-and-go? concept. It aimed to (1) compare previous and old McDonald?s interiors, (2) describe the interior design strategies in the current McDonald?s Greenhills, (3) obtain related customer perception, and (4) determine the effectiveness of the existing McDonald?s interiors in providing a lounging experience.The study was grounded on the theory of semiotics and also used the McDonald?s service scape as the independent variable, with customer response as the intervening one. This qualitative research relied on photo documentation of previous and current McDonald?s interiors, as well as observations of the McDonald?s Greenhills service scape and general dining area. In addition, surveys were given out to 100 respondents to gather customer response regarding the current McDonald?s interior design and experience. The results of the study showed that McDonald?s Greenhills was able to craft an enhanced dining experience through its well-received service scape dimensions, such as color, lighting, music, noise level, smell, room temperature, cleanliness and decorations.Customers saw McDonald?s as a place not just for fast food consumption, but also for work and leisure. While the presence of comfort encouraged lounging among the patrons, it remained within the bounds of what is acceptable in a fastfood setting, such that majority of the patrons confined their stay within an average of 30 minutes.
Thesis (B.S.Interior Design)--University of the Philippines Diliman.
Keywords: Fast food restaurants -- Philippines -- Case studies; MacDonalds -- Philippines (Greenhills, Makati) -- Case studies